Awareness about the role of physical activity and diet on oral health and respiratory health: a questionnaire based cross sectional study - Kavitake, Ranjeet D.; Chand, Sachin; Khan, Mohsin; Shaktawat, Neha; Chauhan, Minal; Chouhan, Dharamveer Singh (International Journal Of Community Medicine And Public Health, 2024)
Background: This cross-sectional study was carried out to assess the awareness of role of diet in oral and systemic health and their inter-relationship amongst the general population of Jodhpur city, Rajasthan. Methods: A cross-sectional epidemiological survey was conducted 800 subjects of Jodhpur city Rajasthan region and a self-constructed questionnaire was used to collect the information. Here patient’s awareness for periodontal-systemic health inter-relationship was also assessed by questionnaire. Study is started conducting from 15th August 2023 to 25th July 2024. Study was completed in 11 months 10 days. Results: It was observed that majority knew about role of diet in oral and respiratory health whereas many of them were not much aware about association of periodontal and systemic conditions which was statistically significant. Conclusions: There is an imperative call for ample educational programs to promote good oral hygiene awareness and its impact on systemic health amongst the general population.